A New National STI and BBV Surveillance System for Aboriginal Community-Controlled Health Services - James Ward; Clare Bradley; Basil Donovan; Belinda Hengel; Salenna Elliott (International Journal of Population Data Science, 2020)
Introduction Aboriginal Community-Controlled Health Services (ACCHSs) routinely collect sexually transmissible infection (STI) and blood-borne virus (BBV) clinical data from individuals through electronic medical records (EMRs). At a population level these data are an underutilised resource and can be used to help drive clinical and public health interventions. Accordingly, we have established a national STI and BBV sentinel surveillance network for ACCHSs —the ATLAS network.